(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article highlights the philosophical significance of shaping a culture of tolerance in young people. The role of the family and society in the formation of a culture of tolerance among young people in connection with morality, as well as the large-scale work carried out in our country are highlighted.